Suplementasi HYPEROL untuk Peningkatan Pertumbuhan Udang Vaname (Litopenaeus vannamei) - Nurul Fatimah; Aldi Huda Verdian; Linuwih Aluh Prastiti; Kurnia Faturrohman; Adni Oktaviana; Qorie Astria; Arif Faisal Siburian (Jurnal Ilmu-ilmu Perikanan dan Budidaya Perairan, 2022)
The provision of quality feed is the most important factor determining the success of vannamei shrimp farming. The aim of this study was to evaluate the growth performance, survival rate and water quality of pacific white shrimp Litopenaeus vannamei after dietary administration of combination of calcium, magnesium dan vitamin D3.  Shrimp were fed a control diet (without combination of calcium, magnesium dan vitamin D3 supplement) and four levels of combination of calcium, magnesium dan vitamin D3 supplementation i.e 0; 0.25; 0.50; 0.75; 1.00 mL Hyperol Kg-1 of feed. Larvae were reared in tank with a dimension of 40x25x30cm containing 4 L of disinfected seawater at a stocking density of 100 larvae m-2. In conclusion, the present study demonstrated that dietary supplementation of combination of at the concentration up to 10 mL Kg-1 could significantly improve growth and survival rate of Pacific white shrimp